Visual Analysis of Chinese Research Teams in Curriculum-based Ideological and Political Education (2014-2021) - Liu, Wei; He, Chunyan (Advances in Social Sciences Research Journal, 2022)
Recent years, research on curriculum-based ideological and political education is one of hotspots in the field of higher education in China. Based on relevant literature of China National Knowledge Infrastructure (CNKI), research field, cooperative relationship between authors and research teams, years of publication and research interests of scholars of 429 papers from 2014 to 2021 on curriculum-based ideological and political education have been analyzed visually with the help of CiteSpace and traditional quantitative research methods. The study has found that research of curriculum-based ideological and political education in China is currently in its growth spurt. However, from research results, the number of publication and cooperation of teams are still in infancy with more potentials in the future.